Pengaruh Manajemen Kelas Oleh Guru Terhadap Disiplin Belajar Siswa Kelas XI di SMK Swasta HKBP Sidikalang - Nami Sri Devi; Robinhot Sihombing; Endang Juliati Manullang; Lasmaria Lumban Tobing (BADAN PENERBIT STIEPARI PRESS, 2024)
The aim of this research is to determine the influence of classroom management by teachers on the learning discipline of class XI students at HKBP Sidikalang Private Vocational School. The method used in this research is an inferential quantitative approach. The population is all class Data was collected using a positive closed questionnaire with 40 items. The results of data analysis show that classroom management by teachers has a positive and significant effect on student learning discipline at HKBP Sidikalang Private Vocational School. Test the analysis requirements in this research using the normality test to obtain the Asymp value. Sig. (2-tailed) is 0.200, meaning it is greater than 0.05 (0.200 > 0.05) so it can be concluded that the research data is normally distributed. The results of the correlation test show that there is a positive relationship between variable Apart from that, the significant relationship test obtained a value of tcount= 6.753 > ttable(=0.05, dk=n-2=72)= 2.000, thus there is a significant relationship between variable X and variable Y. The hypothesis was tested through a regression equation test, obtained the regression equation Y ̂=13.810+0.807 X and the regression coefficient of determination test (r2) = 38.1%. Testing the hypothesis using the F test obtained Fcount > Ftable, namely 45.597 > 4.00. Thus Ha is accepted and H0 is rejected. So it can be concluded that classroom management by teachers has a positive and significant effect on the learning discipline of class XI students at HKBP Sidikalang Private Vocational School.